Proliferative fasciitis of the chin: A report of the rare case and review of literature - H Jyothi; S Sudha; Resmi G Nair; K Remya (Wolters Kluwer Medknow Publications, 2019)
Proliferative fasciitis is a pseudo-sarcomatous myofibroblastic proliferation characterized by the presence of unusual giant cells resembling ganglion cells, which usually occurs in the adult population with a mean age of 54 years. It usually affects the upper extremities and is rare in head and neck region with only 11 cases described in the literature so far. Because of rapid growth and histological similarity to various malignant tumors such as rhabdomyosarcoma, recognition of this benign condition is a matter of utmost importance when a pathologist is concerned. In this study, we report a case of a 11-year-old boy presented with a lesion on the right side of chin, along with a literature review involving those cases reported in the head and neck region.